Continuous-flow system and monitoring tools for the dielectrophoretic integration of nanowires in light sensor arrays. (27th February 2015) - Marín, A García; Núñez, C García; Rodríguez, P; Shen, G; Kim, S M; Kung, P; Piqueras, J; Pau, J L
Abstract: Although nanowires (NWs) may improve the performance of many optoelectronic devices such as light emitters and photodetectors, the mass commercialization of these devices is limited by the difficult task of finding reliable and reproducible methods to integrate the NWs on foreign substrates. This work shows the fabrication of zinc oxide NWs photodetectors on conventional glass using transparent conductive electrodes to effectively integrate the NWs at specific locations by dielectrophoresis (DEP). The paper describes the careful preparation of NW dispersions by sedimentation and the dielectrophoretic alignment of NWs in a home-made system. This system includes an impedance technique for the assessment of the alignment quality in real time. Following this procedure, ultraviolet photodetectors based on the electrical contacts formed by the DEP process on the transparent electrodes are fabricated. This cost-effective mean of contacting NWs enables front-and back-illumination operation modes, the latter eliminating shadowing effects caused by the deposition of metals. The electro-optical characterization of the devices shows uniform responsivities in the order of 10 6 A W −1 below 390 nm under both modes, as well as, time responses of a few seconds.